Impact of Soft Tissue Pathophysiology in the Development and Maintenance of Bisphosphonate-Related Osteonecrosis of the Jaw (BRONJ) - Thomas Ziebart; Frank Halling; Paul Heymann; Andreas Neff; Sebastian Blatt; Junho Jung; Andreas Pabst; Leonardo Righesso; Christian Walter (Dentistry Journal, 2016)
Since the first description of bisphosphonate-related osteonecrosis of the jaw (BRONJ), numerous research groups have focused on possible pathological mechanisms including the suppression of the bone turnover of the jaw, antiangiogenic effects and soft tissue toxicity. In our review we focused on summarizing the role of the soft tissues in the development and progression of BRONJ. The biological behavior of fibroblasts can be significantly influenced by bisphosphonates (BP) such as a concentration dependent reduction of cell viability. High concentrations of BP can induce apoptosis and necrosis of the cells. Comparable effects could be detected for keratinocytes. Compared to non-nitrogen containing bisphosphonates, nitrogen-containing BP have worse effects on cell biology by blocking the mevalonate pathway. Further, the cell architecture and expression levels of several genes and proteins are significantly disturbed by BP. These inhibitory effects of BP are in accordance with BP-related reduced angiogenesis and neovascularization and could underline the hypothesis that inhibition of fibroblasts and keratinocytes results in delayed wound healing and can induce and trigger BRONJ.